Effect of earthquakes on spontaneous pneumothorax development (Annals of Medical Research, 2021)
Aim: This study researched the effect of earthquakes, affecting meteorological parameters by causing pressure changes in the atmosphere, on the development of spontaneous pneumothorax (SP) and which periods after earthquakes were risky in terms of SP development. Material and Methods: The study retrospectively investigated the files of 117 cases, 4 females (3.4%) and 113 males (96.6%) with spontaneous pneumothorax diagnosis in the emergency service of our hospital within a five-year period. The day patients attended hospital was accepted as the day of pneumothorax formation. Meteorological data for the study period was obtained from the Republic of Turkey General Directorate of Meteorology. Earthquake data for the study period were obtained from the Earthquake Department of the Republic of Turkey Disaster And Emergency Management Presidency website. The correlation of the changes in air temperature, humidity and pressure values of the day on which SP occurred compared to the previous day was investigated with SP. Additionally, risk analysis was performed for the correlation of SP formation time with earthquake days and the time interval after earthquakes.Results: Within the study duration, the number of SP cases on the same day as earthquakes in the region was 27, with earthquake magnitude a minimum of 2.10 and maximum of 4.00 with mean of 2.5±0.47 calculated. Cases attending on days without earthquakes (n=90) were assessed in terms of how many days after the last earthquake they attended and mean duration was 8.14±8.03 days, with attendance due to pneumothorax a minimum of 1 day and maximum 44 days later. As the duration after an earthquake lengthened, there was a statistically significant reduction in the number of attendances.Conclusion: SP is a clinic that can be diagnosed initially by doctor suspicion. In our study, we identified earthquakes were effective on pneumothorax development. As a result, we believe it is necessary to initially consider SP diagnosis for cases attending the emergency department with dyspnea and chest pain complaints in this risky period.
Keywords: Earthquake; pressure; spontaneous pneumothorax (SP)